“IT’S BELOW MY EXPECTATION”: A CASE STUDY OF UMN ONLINE LEARNING STUDENT - Alvin, Silvanus (RADJA PUBLIKA, 2023)
Online learning has grown in popularity in Indonesia, particularly among people looking to gain new skills or improve their existing knowledge. The COVID-19 epidemic has exacerbated this tendency by necessitating the use of remote learning approaches. This study aims to discover students' initial expectations when they enroll UMN and the reality after they become UMN online learning students The urgency of this research is based on the fact that the dropout rate at UMN is roughly 28%. Dropout may be harmful to both the individual student and the institution, thus it is critical to address the underlying reasons of dropout and develop effective ways to encourage student success and retention. The gap between expectation and reality is crucial to understand because it can influence the creation or modification of policies designed to protect students from dropping out. This qualitative research applies data collection using FGDs involving 40 UMN online learning program students. One of the most interesting findings from this research is that online learning students were surprised to learn about the SKKM policy, which they did not expect. The majority of students who are workers admitted that it was difficult to set aside time to do additional activities to collect SKKM points.